2021
DOI: 10.3389/fcell.2020.627436
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effect of Differentially Expressed Long Non-coding RNAs Driven by Copy Number Variation on Competing Endogenous RNA Network by Mining Lung Adenocarcinoma Data

Abstract: Lung cancer is the first cause of cancer death, and gene copy number variation (CNV) is a vital cause of lung cancer progression. Prognosis prediction of patients followed by medication guidance by detecting CNV of lung cancer is emerging as a promising precise treatment in the future. In this paper, the differences in CNV and gene expression between cancer tissue and normal tissue of lung adenocarcinoma (LUAD) from The Cancer Genome Atlas Lung Adenocarcinoma data set were firstly analyzed, and greater differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Many lncRNAs including ITGB1-DT [ 10 ], LINC01426 [ 11 ], UPLA1 [ 12 ] have been revealed to promote LUAD cell migration and invasion. Mechanistically, the competing endogenous RNA (ceRNA) pattern has been widely reported to be involved in LUAD progression [ 13 15 ]. The ceRNA network refers to that lncRNAs bind with microRNAs (miRNAs) to suppress the degradation of the targets of the miRNAs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many lncRNAs including ITGB1-DT [ 10 ], LINC01426 [ 11 ], UPLA1 [ 12 ] have been revealed to promote LUAD cell migration and invasion. Mechanistically, the competing endogenous RNA (ceRNA) pattern has been widely reported to be involved in LUAD progression [ 13 15 ]. The ceRNA network refers to that lncRNAs bind with microRNAs (miRNAs) to suppress the degradation of the targets of the miRNAs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…AC022784.1 (12), TDRKH-AS1 (29), and LINC00941 (29) had been reported to be associated with the prognosis of LUAD. LINC00942, LINC01116, SNHG4, MIR31HG, and LINC00460 had been known to be associated with tumor development and progression and drug resistance in various cancers including lung cancer (30)(31)(32)(33)(34)(35)(36)(37)(38)(39). AC107959.3 (40) and LINC02154 (41) were reported to be associated with the prognosis of hepatocellular carcinoma and laryngeal cancer respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, LINC00942 was identified as one of four immune-related lncRNAs to predict prognosis and immunotherapy efficiency in bladder cancer patients ( 31 ). It also reported that LINC00942 was identified as one of the two components in a ceRNA network associated with gene number copy variation, which can be used to predict tumor response to drug treatment in patients with lung adenocarcinomas ( 32 ). Initially, LINC00858 was identified as a ceRNA impacting miR-422a to control the expression of kallikrein-related peptidase 4, and its high expression was found to be closely correlated to tumor progression of non-small cell lung carcinomas ( 33 ).…”
Section: Discussionmentioning
confidence: 99%